The workload of the interventional cardiology centers from Romania: a 2023-2024 overview and 2014-2024 trends - Predescu Lucian M.; Câlmâc Lucian (Romanian Journal of Cardiology)
This article presents data on the workload of interventional cardiology centers in Romania for the years 2023 and 2024. All interventional cardiology centers in Romania were requested to complete a standardized form, documenting the total number of various procedures performed throughout 2023-2024. The report presents the total number of coronary interventions, peripheral interventions, and structural heart disease interventions conducted in Romania in 2023 and 2024. Additionally, it includes a comparison of the workload of these centers from 2014 to 2024.